In Vivo Anticoagulant and Antiplatelet Effect of D-Phe-Pro-Arg-H and D-MePhe-Pro-Arg-H - Bagdy, Dániel; Barabás, Éva; Szabó, Gabriella; Bajusz, Sándor; Széll, Erzsébet (Thrombosis and Haemostasis, 1992)
D-Phe-Pro-Arg-H and D-MePhe-Pro-Arg-H synthetized in our institute were administered to mice, rats, rabbits and beagle dogs. The kinetics of the anticoagulant and antiplatelet effect was recorded by measuring various clotting parameters, platelet count and aggregation, and evaluated as proposed by Verstraete and Verwilghen. The minimum effective doses were found to be 0.25-0.5 mg kg-1h-1 by intravenous continuous infusions and 0.5-1.0 mg/kg by single injections. The dose-dependent prolongation of clotting times appeared after application within minutes and returned to baseline values as a function of dose. Blood level of the inhibitors was determined by a bioassay. Unlike heparin, no higher starting dose was required to reach the anticoagulant threshold level, i.e. 0.03-0.1 ¼g/ml whole blood. The peptides did not cause significant changes in platelet count and function or in hemodynamic parameters (blood pressure, heart rate and ECG) and in respiration. They blocked platelet aggregation induced by thrombin ex vivo specifically. No rebound effect or bleeding could be demonstrated even after subtoxic doses of the compounds. The onset of the anticoagulant and antithrombotic effect appeared within 60 min after single oral doses and lasted for 3-6 h. In close correlation with the anticoagulant effect a complete or significant inhibition of platelet aggregation induced by thrombin ex vivo could also be recorded by using 5-10 mg/kg doses.